WILD EDIBLE MUSHROOMS OF MEGHALAYA - Barua, Paran (Medknow Publications & Media Pvt Ltd, 1998)
Different flesh mushrooms grow widely in Meghalaya. Altogether fie edible species were collected and identified which were found abundantly in forest and are known to be consumed by local people for time immemorial, The species identified are lentinus edodes (Berk) Sing., Boletus edulis Bull ex Fr., Clavaria cinerea (Fr.) Schroet, Clavaria aurea (F) Quet and cantharellus floccosus Juss.